Information Technology Service Management with Cloud Computing Approach to Improve Administration System and Online Learning Performance - Wilianto, Wilianto; Fitri, Iskandar (CommIT (Communication and Information Technology) Journal, 2015)
This work discusses the development of information technology service management using cloud computing approach to improve the performance of administration system and online learning at STMIK IBBI Medan, Indonesia. The network topology is modeled and simulated for system administration and online learning. The same network topology is developed in cloud computing using Amazon AWS architecture. The model is designed and modeled using Riverbed Academic Edition Modeler to obtain values of the parameters: delay, load, CPU utilization, and throughput. The simu- lation results are the following. For network topology 1, without cloud computing, the average delay is 54  ms, load 110 000 bits/s, CPU utilization 1.1%, and throughput 440  bits/s.  With  cloud  computing,  the  average  delay  is 45 ms,  load  2 800  bits/s,  CPU  utilization  0.03%,  and throughput 540 bits/s. For network topology 2, without cloud computing, the average delay is 39  ms, load 3 500 bits/s, CPU utilization 0.02%, and throughput database server 1 400 bits/s. With cloud computing, the average delay is 26 ms, load 5 400 bits/s, CPU utilization email server 0.0001%, FTP server 0.001%, HTTP server 0.0002%, throughput email server 85 bits/s, FTP    server 100 bits/sec, and HTTP server 95  bits/s.  Thus,  the  delay, the load, and the CPU utilization decrease; but,  the throughput increases. Information technology service management with cloud computing approach has better performance.